1996
DOI: 10.1021/es960306z
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins in the Environment:  A Review of Trend Data

Abstract: A comprehensive review of available PCDD/F time trend data is presented. This focuses on industrialized countries, drawing heavily on those countries that have been actively involved in PCDD/F monitoring and research, notably Germany, the United States, Sweden, The Netherlands, and the U.K. Information on temporal trends comes from the analysis of dateable deposits (e.g., sediments), retrospective analysis of preserved or archived samples, and ongoing monitoring programs. The data on changes in air concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(134 citation statements)
references
References 75 publications
6
127
0
1
Order By: Relevance
“…PCDD and PCDF are formed as side products in chlorophenol production and in thermic reactions, such as combustions and chlorinations but also in pulp and paper production (Alcock and Jones 1996;Kim et al 2002). In pulp production, the PCDD and PCDF are mostly formed by condensation of polychlorinated phenoxyphenols in pulping and by chlorination of dibenzofuran and dibenzo-p-dioxin in pulp bleaching (Hrutfiord and Negri 1992;Luthe and Berry 1996;Yunker et al 2002).…”
Section: Chlorinated Organic Compoundsmentioning
confidence: 99%
“…PCDD and PCDF are formed as side products in chlorophenol production and in thermic reactions, such as combustions and chlorinations but also in pulp and paper production (Alcock and Jones 1996;Kim et al 2002). In pulp production, the PCDD and PCDF are mostly formed by condensation of polychlorinated phenoxyphenols in pulping and by chlorination of dibenzofuran and dibenzo-p-dioxin in pulp bleaching (Hrutfiord and Negri 1992;Luthe and Berry 1996;Yunker et al 2002).…”
Section: Chlorinated Organic Compoundsmentioning
confidence: 99%
“…1 Of the 75 PCDDs and 135 PCDFs, the seventeen 2,3,7,8-substituted congeners are most toxic and have been assigned toxic equivalent factors (TEFs). 2,3 Atmospheric transport is considered as a major pathway for the transfer of PCDD/Fs to terrestrial and aquatic ecosystems.…”
Section: ' Introductionmentioning
confidence: 99%
“…In soils, the extremely hydrophobic substances, such as chlorinated hydrocarbons, are very immobile and thus are not readily available for root adsorption or subsequent uptake MuK ller et al, 1994;Fries, 1995). Transport of PCDD/Fs within plants is considered to be unlikely, even over long time intervals Alcock and Jones, 1996). Plant uptake studies with 2,3,7,8-TCDD in growth chambers and 1,2,3,4-TCDD in greenhouse have demonstrated that volatilization from soil, rather than root uptake and translocation, is the main pollution source in plants (McCrady et al, 1990;Bacci et al, 1992).…”
Section: Discussionmentioning
confidence: 99%